1997
DOI: 10.1046/j.1365-2265.1997.d01-1736.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on serum levels of dehydroepiandrosterone metabolites in men

Abstract: These results suggest that insulin increases the DHEA metabolic clearance rate by stimulating its conversion to DHEA-FA and by enhancing uptake of DHEA-FA by peripheral tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…On the other hand, Nestler et al reported a progressive decreasement in serum DHEAS levels in women during a hyperinsulinemic-euglycemic clamp study. They found the same decrement in the androstenedione levels too [27][28][29][30]. Various mechanisms of insulin-induced reduction of serum levels of adrenal androgens can be considered.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Nestler et al reported a progressive decreasement in serum DHEAS levels in women during a hyperinsulinemic-euglycemic clamp study. They found the same decrement in the androstenedione levels too [27][28][29][30]. Various mechanisms of insulin-induced reduction of serum levels of adrenal androgens can be considered.…”
Section: Discussionmentioning
confidence: 79%
“…Rather, data suggest that hyperinsulinemia enhances the metabolic clearance of DHEAS, and that this mechanism might be responsible for the rapid decrease of DHEAS [17]. In fact, other studies that investigated the alteration of DHEAS under reactive physiological hyperinsulinemia could not demonstrate such a great decrease in DHEAS as those carried out under supraphysiological hyperinsulinemia [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been proposed that reduced DHEA may mediate the relationship with an increased risk of cardiovascular disease through a diminished inhibition of fibroblast growth and differentiation, alterations in the plasma lipid profile and through a diminished inhibition of platelet aggregation (88). It has also been shown that insulin may increase the metabolic clearance of DHEA (89), and studies by our group have demonstrated that hyperinsulinemia induced during DHEA infusion stimulated DHEA fatty acid esterification through the action of plasma lecithin: cholesterol acyltrasferase (90). On the other hand, DHEA-S may have direct effects on insulin sensitivity by increasing insulin binding to its own receptor (91).…”
Section: Insulin Resistance and Hyperinsulinemiamentioning
confidence: 93%